2017
DOI: 10.1615/jlongtermeffmedimplants.2017019926
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Strain Distribution Patterns in Bone around Splinted Standard and Short Implants Placed at the Crestal Level and Subcrestally using Three- Dimensional Finite Element Analysis

Abstract: Short implants can be used as alternatives to standard implants to prevent invasive surgical procedures. However, due to concerns about complications caused by less bone-implant contact area, researchers have focused on biomechanical properties of short implants and methods to promote them. Splinting has been suggested to decrease the limitation of short implants. This study compared the pattern of stress and strain distribution in bone supporting splinted standard and short implants positioned at crestal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
2
1
1
Order By: Relevance
“…Quantitatively, the axial loading showed that the greatest angulation (30°) resulted in low stress peaks and the risk of bone loss. In turn, Amid et al ( 20 ) observed that the application of an axial loading at 100 N and 30° angle caused more stress when compared to the axial application of 300 N along the axis of implants, presenting different results from those found in the present study. For the oblique loading, quantitatively, there was an inversion of the trends found for the axial loading, in which the greatest angulation of the implant elevated the stress peaks.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Quantitatively, the axial loading showed that the greatest angulation (30°) resulted in low stress peaks and the risk of bone loss. In turn, Amid et al ( 20 ) observed that the application of an axial loading at 100 N and 30° angle caused more stress when compared to the axial application of 300 N along the axis of implants, presenting different results from those found in the present study. For the oblique loading, quantitatively, there was an inversion of the trends found for the axial loading, in which the greatest angulation of the implant elevated the stress peaks.…”
Section: Discussioncontrasting
confidence: 96%
“…For the oblique loading, quantitatively, there was an inversion of the trends found for the axial loading, in which the greatest angulation of the implant elevated the stress peaks. The data corroborate Amid et al ( 20 ), who obtained maximum stress on the peri-implant bone when applying oblique loading at a 30° angle.…”
Section: Discussionsupporting
confidence: 91%
“…Ancak kısa implantlar için, beş yıldan uzun bir takip sürecine, prognozları hakkında daha fazla bilgiye ihtiyaç duyulmaktadır. 33…”
Section: Introductionunclassified
“…17,18 However, other studies reported that implant placement at the crestal bone level was better for stress distribution. 19,20 Therefore, due to the absence of consensus, biomechanical evaluation of this parameter is necessary, as bone preservation is important for the aesthetic success of rehabilitation. 5,20,21 This is particularly applicable for narrow-diameter Morse taper implants placed in the atrophic maxillary anterior region.…”
mentioning
confidence: 99%
“…Regarding biomechanical evaluation, some studies reported that the stress in the peri‐implant bone decreased as the implant depth has been increased 17,18 . However, other studies reported that implant placement at the crestal bone level was better for stress distribution 19,20 . Therefore, due to the absence of consensus, biomechanical evaluation of this parameter is necessary, as bone preservation is important for the aesthetic success of rehabilitation 5,20,21 .…”
mentioning
confidence: 99%